2021
DOI: 10.1108/jhom-12-2020-0474
|View full text |Cite
|
Sign up to set email alerts
|

That's how it should work: the perceptions of a senior management on the value of decentralisation in a service delivery organisation

Abstract: PurposeDecentralisation in health care has been proposed as a way to make services more responsive to local needs and by that improve patient care. This study analyses how the senior management team conceptualised and implemented a decentralised management model within a large public health care delivery organisation.Design/methodology/approachData from in-depth interviews with a senior management team were used in a directed content analysis. Underlying assumptions and activities in the decentralisation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The aim of management decentralisation within a healthcare organisation is to improve resource utilisation to better match to patients’ needs and adapt to local conditions. The focus is on organisational performance and efficiency as shown in empirical studies of service delivery organisations outside the hospital environment [ 4 , 5 ]. In this study we have had the opportunity to explore if a decentralised service provider showed organisational agility when struck by unexpected turbulence caused by the outbreak of the Covid-19 pandemic,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of management decentralisation within a healthcare organisation is to improve resource utilisation to better match to patients’ needs and adapt to local conditions. The focus is on organisational performance and efficiency as shown in empirical studies of service delivery organisations outside the hospital environment [ 4 , 5 ]. In this study we have had the opportunity to explore if a decentralised service provider showed organisational agility when struck by unexpected turbulence caused by the outbreak of the Covid-19 pandemic,…”
Section: Discussionmentioning
confidence: 99%
“…There is a general consensus that these principles are shown to be valid on a systems level in public healthcare [ 1 3 ]. Our studies of one large healthcare service delivery organisation in Sweden indicate that the same mechanisms work intra-organisationally [ 4 , 5 ]. When applying management decentralisation at the organisational level the main objective and focus are, consequently, on promoting organisational performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings were previously reported in detail in the a priori programme theory evaluation of the management model. 10…”
Section: Methodsmentioning
confidence: 99%
“…A semi-structured interview guide with open-ended questions was used, addressing the three components in the revised Bossert 12 model of management decentralisation. 10…”
Section: Methodsmentioning
confidence: 99%